The Influence of Halal Awareness, Knowledge and Regulations on Submitting Halal Self Declare Certification for Micro and Small Business Actors in the Culinary Sector in Pacet District, Mojokerto Regency - Salsabila, Aulia Ziyadaturrahmah; Kalimah, Siti (Iqtishodia: Jurnal Ekonomi Syariah, 2024)
L Law No.33 concerning Halal Product Guarantees requires halal certification for every product imported and distributed. and traded in Indonesian territory. MSEs are the target of BPJPH in applying for halal certification. This research is to answer the question of whether there is a significant influence between halal awareness, knowledge and regulations simultaneously or partially on the application for halal certification among MSEs in the culinary sector in Pacet Mojokerto. This research uses a quantitative approach method with data collection techniques, namely questionnaires distributed to respondents. The research results obtained show that halal awareness, knowledge and regulations simultaneously have a positive and significant influence on applications for halal self-declaration certification of 0.627 or 62.7%. Then for partial testing, the halal awareness variable has a positive but not significant effect on the application for self-declared halal certification. Meanwhile, the knowledge and regulatory variables have a positive and significant effect on applications for halal self-declaration certification among MSEs in the culinary sector in Pacet, Mojokerto. This research provides recommendations for the government, becomes evaluation material in determining policy direction, and provides support and outreach regarding halal certification. For institutions applying for halal certification in Pacet Mojokerto, evaluation and improvement materials for halal certification assistance so that it can be maximized. And for business actors to pay more attention to having halal certification for each of their products.